الأديان عند الشهرستاني (ت 548 هـ) : دراسة تحليلية نقدية مقارنة - مسعود، يثرب عوض السيد أحمد (Kulliyah of Islamic Revealed Knowledge and Human Sciences, International Islamic University Malaysia, 2002)
This is a critical, analytical and comparative study to al-Shahristani's encyclopedic work, which is known as Kitab al-Mila/ wa 'al-Nihal. This study focuses on Christianity, Judaism and Magian section of Kitab al-Mila/ wa 'a/Nihal. The main purpose of the research is to examine al-Shahristani's methodology in studying other religions. Al-Shahristani was a prominent scholar of comparative religion but researchers did not study the work analyzed by this study, Muslim sects, thoroughly. The main questions of this study are: what are the principles, approaches, and conditions drawn and followed by al-Shahristani in studying; Christianity, Judaism and Magian in his book. The study found the following: First: The main theme of al-Shahristani's book, Kitab al-Mila! wa 'al-Nihal, is the dominance of reporting or narrative approach in explaining Christianity and Judaism. As for the part on Magian, he deviates from this methodology. He pays more attention to this belief providing more criticism and commentary. Second: in the part of the book about Christianity, Judaism and Magian, it is not possible to trace sources. Views of sects were reported without reference to their ongm. Third: the study revises many aspects of historical facts and definitions in the study and presents, more importantly, a comprehensive and neutral treatment of Christianity, Judaism and Magian beliefs. The researcher hopes that this study may represent an additional scientific contribution in this field.